التأصيل المفاهيمي للأمن المجتمعي Conceptual rooting of Societal Security - بن سالم رضا; ربيج شداد (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
يعتبر القطاع المجتمعي أحد الميادين الأساسية للأمن بمفهومه الموسع في ظل المخاطر الأمنية التي يشهدها العالم خاصة بعد الحرب الباردة، فظهر مفهوم الأمن المجتمعي كبعد من أبعاد الأمن الذي يرتبط أساسا بمعيار التنمية المستدامة في مختلف مجالات الحياة. يبقى البحث عن مفهوم الأمن المجتمعي مجال المهتمين والباحثين في ظل فشل البرامج التنموية وغياب إستراتيجية فعالة كفيلة بضمان حياة كريمة سواء من الناحية الاقتصادية أو الاجتماعية أم من ناحية المشاركة في الحياة السياسية وتحقيق الديمقراطية. The community sector is considred one of the basic fields of security in its expanded concept in the light of the security risks that the world in witnessing especilally aftre the cold war as the concept of societal security appeared which is the dimension of security and is mainly related to the standard of sustainable development for various areas of life. The search for the consept of of societal security remains the domain of interested and researchers in the light of the failure of development programs and the absence of an effective strategy that guarantees a decent life in terms of economic or social terms, or in terms of participating in political life and achievement of democracy.